On Christian doctrine - Augustine, Saint, Bishop of Hippo, 354-430 (Library of liberal arts ;, 1958)
"This translation of St. Augustine's De doctrina Christiania is based on the Benedictine text. Quotations from the Bible appear in the Douay-Rheims version, but the footnotes contain reference in brackets to indicate the location of corresponding verses in the King James Bible where the Bible contains the same material arranged according to a different system. Essentially, On Christian Doctrine is an introduction to the interpretation and explanation of the Bible."--Translator's preface and introduction.